Surgical techniques for degenerative cervical spine in Finland from 1999 to 2015 - Kotkansalo A.; Malmivaara A.; Korajoki M.; Korhonen K.; Leinonen V. (SPRINGER WIEN, 2022)
Purpose: The purpose of this study is to assess the trends and regional variations in the operative techniques used for degenerative or rheumatoid cervical spine disease in Finland between 1999 and 2015.
Methods; The Finnish Hospital Discharge Register (FHDR) was searched for the data on all the primary operations for degenerative cervical spine disease (DCSD) or rheumatoid atlanto-axial subluxation (rAAS). Operative codes were used to identify the patients from the FHDR and combined with diagnosis codes to verify patient inclusion. The patients were classified into three groups: anterior cervical decompression and fusion (ACDF), posterior decompression and fusion (PDF) and decompression.
Results: A total of 19,701 primary operations were included. The adjusted incidence of ACDF rose from 6.5 to 27.3 operations/100,000 adults. ACDF became the favoured technique in all the diagnostic groups except AAS, and by 2015, ACDF comprised 84.5% of the operations. The incidence of PDF for DCSD increased from 0.2 to 0.7/100,000 people. Solely decompressive operations declined from 13.7 to 4.0 operations/100,000 people. The regional differences in the incidence of operations were most marked in the incidence of ACDF, with overall incidences ranging from 11.2 to 37.0 operations/100,000. The distribution of the operative techniques used varied as well.
Conclusions: Between 1999 and 2015, the operative techniques used for DCSD changed from prevalently decompressive to utilising ACDF in 68.8 to 91.0% of the operations, depending on the treating hospital. ACDF became the most commonly applied technique for all degenerative diagnoses except AAS.